Revisión de literatura de la bacterioterapia en la inhibición del crecimiento del Streptococcus mutans - Alfonso Zabala, Kathleen Julieth; Estrada Torres, Leidy Juliana (Universidad Antonio Nariño, 2021)
Introduction: Dental caries continues to be a problem in public health, taking great importance in the fields of diagnosis and prevention.